Risk factors of muscular discomfort among motorcyclist-review article - Alias, Ayuni Nabilah; Karuppiah, Karmegam; Mohd Tamrin, Shamsul Bahri; Zainal Abidin, Emilia; Mohd Shafie, Umi Kalsom; Sambasivam, Sivasankar (Tehran University of Medical Sciences, 2016)
Background: Motorcycle has been one of the vital modes of transportation worldwide. It is quite difficult to identify the risk factors that affect muscular discomfort among motorcyclist due to not much research having been carried out on the motorcyclist. The purpose of this study was to have a better understanding of the risk factors of muscular discomfort among motorcyclist due to motorcycle riding. Method: Five databases were searched based on keywords that related to the risk factors might cause discomfort among motorcyclist. The research screened covered years between 1973 until 2013. In order to identify and classify research studies, specific keywords were identified and used in order to guide the discovery of relevant studies. Result: As overall, five risk factors were identified that might affect the muscle activity and cause discomfort on various parts of body among motorcyclist. Risk factors such as biological, environmental, vehicle, physiological and life activities factors were related to each other and might contribute to the discomfort among motorcyclists during riding process. Conclusion: This review was done to relate risk factors of muscular discomfort among motorcyclist, as there is currently not much information available on the riding and muscular discomfort of motorcyclists in Malaysia.